ENDING IN IMPROVING SKILLS AND PROVIDING MILLING EQUIPMENT FOR CASSAVA SKIN PROCESSING INTO HEALTHY AND ECONOMICALLY VALUABLE SNACKS: PENDAMPINGAN DALAM PENINGKATAN KETERAMPILAN DAN PEMBERIAN PERALATAN PENGGILINGAN UNTUK PENGOLAHAN KULIT SINGKONG MENJADI SNACK SEHAT DAN BERNILAI EKONOMIS - Umi Salmah; Sri Malem Indirawati; Yenny Obsi Satra (Yayasan Education and Social Center, 2021)
This community service aims to provide Partners with skills improvement assistance through using training (online tutorials via video) in order to improve family nutritional status and family income, as well as improve the quality of environmental health. The method of processing the cassava peel is done by collecting the cassava peel, cleaning it, then boiling it using a technique of reducing cyanide levels and drying it in the sun. The next stage is mashed into flour then mixed with vegetable protein sources and processed into a snack with a variety of flavors and shapes. The activity in this dedication is by presenting tutorials to business groups by presenting a youtube link on how to make multipurpose flour from cassava peels. This activity provides knowledge and skills improvement for partners in processing cassava peels to partners (through providing video tutorials on how to process cassava peels into multipurpose flour) was prepared by the mentor. The activity in this community service is by presenting tutorials to business groups by presenting a youtube link on how to make all-purpose flour from cassava peels. This activity give knowledge and skills improvement for partners in processing cassava peels to partners (through presenting video tutorials on how to process cassava peels into multipurpose flour) was prepared by the mentor. Mashed cassava, corn and rice. The ffc 15 flour machine can flour up to 5-10Kg / hour. The ffc 15 flour machine has 3 size filters for flouring as needed